POTTERY TRADITION OF THE EARLY MEDIEVAL POPULATION OF THE VERKHNY CHIRYURT - Suhanov, Evgenij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2023)
In the 8th century, the Saltovo-Mayaki archeological culture was forming under the influence of the population, migrated to the Don basin from the territory of the North Caucasus. Despite the extensive history of studying Saltovo-Mayaki antiquities, it is still unknown people of which North Caucasian regions took part in this resettlement and impacted the development of cultural traditions of the Don region in the 8th – 10th centuries. To solve this issue, the author proposes to create a database of pottery traditions of the early-medieval populations of various regions of the North-Caucasus. Such a database will allow to discuss the directions of migration of the North Caucasian population to the Don basin, based on mass archeological material. The paper presents first results of work on this scientific project. The subject of our research is the ceramic ware from the complex of sites of the Khazar era in the eastern regions of the North Caucasus – the fortified settlement of Verkhnyi Chiryurt, located in the territory of Coastline Dagestan. The paper aims to introduce to the public the results of the technical and technological study of pottery and the reconstruction of specific pottery traditions of the inhabitants of Verkhnyi Chiryurt. The study was carried out according to the method, developed by A.A. Bobrinsky – the author of the historical-cultural approach to studying ancient pottery. 94 samples of ceramic ware were analyzed. Two technological traditions of pottery production, which existed among the early medieval inhabitants of the Verkhnyi Chiryurt settlement, have been reconstructed. The use of poorly sanded, relatively “clean” natural impurities in the composition of clay, the addition of mineral and organic tempers to the clay body, the application of bands in the formation of vessels and various firing methods have been recorded as distinctive features of the techniques of representatives of the first tradition. The techniques of the bearers of the second tradition are characterized by the use of medium-grained, relatively “impure” clay, the addition of only organic tempers to the clay body, the use of cords in the design of the vessel, the use of reduction firing, and, in some cases, of black-polishing.
Keywords: pottery tradition; ceramic ware; Verkhnyi Chiryurt; Saltovo-Mayaki